2000
DOI: 10.2134/agronj2000.922206x
|View full text |Cite
|
Sign up to set email alerts
|

Malate, Citrate, and Amino Acids in Tall Fescue Cultivars: Relationship to Animal Preference

Abstract: Grazing animals depend on little‐understood chemical and physical cues when selecting forage diets. This study determined malate, citrate, and amino acid concentrations in endophyte‐free tall fescue (Festuca arundinacea Schreb.) and related those concentrations to cultivar, harvest time, and grazing‐animal preference. ‘Barcel’, ‘Kenhy’, ‘Kentucky‐31’, ‘Missouri‐96’, ‘Mozark’, ‘Stargrazer’, and the two accessions C1 and HiMag were established in three replicates within each of three pastures. Organic acids were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Simple sugars, starch, fructans, soluble fiber, and organic acids comprise NFC, while TNC does not include organic acids or soluble fibers such as pectins (Hall, 2007). Mayland et al (2000a) reported that organic acid concentration was not related to diet preference of cattle among eight tall fescue cultivars.…”
Section: Resultsmentioning
confidence: 95%
“…Simple sugars, starch, fructans, soluble fiber, and organic acids comprise NFC, while TNC does not include organic acids or soluble fibers such as pectins (Hall, 2007). Mayland et al (2000a) reported that organic acid concentration was not related to diet preference of cattle among eight tall fescue cultivars.…”
Section: Resultsmentioning
confidence: 95%
“…These changes will likely have a major negative impact on timothy regrowth potential ( Jing et al, 2014 ) and thus, on the supply of quality timothy forage to meet the cattle industry dietary needs ( Piva et al, 2013 ). Grazing animals depend on a variety of chemical cues when selecting which plants they will eat, with soluble energy (i.e., free amino acids and organic acids and water-soluble carbohydrates) being the primary factor for selection ( Maryland et al, 2000 ; Tamoura et al, 2009 ).…”
Section: Introductionmentioning
confidence: 99%
“…Nonfiber carbohydrates (NFC) were calculated in this study (TNC + organic acids and soluble fiber) and were greater in alfalfa at both times of day, so organic acids and/or soluble fiber may be influencing the greater preference for alfalfa. However, Mayland et al (2000a) reported that organic acid concentration was not related to diet preference of cattle among eight tall fescue cultivars.…”
Section: Resultsmentioning
confidence: 95%